Peran Budaya Konsumen Sebagai Variabel Moderasi Terhadap Pengaruh Service Quality terhadap Customer Loyalty pada Produk Herbal di Surabaya - Helfi Alfionita; Handy Aribowo (Jurnal Manajemen dan Budaya, 2026)
This study aims to examine the influence of service quality on customer loyalty, with consumer culture serving as a mediating variable, within the context of herbal products in Surabaya. A quantitative approach was employed using a survey method with a 1–4 Likert scale questionnaire distributed to 110 respondents selected via purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM). The results indicate that service quality has a positive and significant influence on customer loyalty. Furthermore, consumer culture was found to mediate this relationship by strengthening the impact of service quality on customer loyalty. These findings demonstrate that cultural aspects play a crucial role in shaping loyal consumer behavior, particularly regarding herbal products, which are closely linked to traditional values. The study's implications highlight the importance of enhancing service quality and understanding consumer culture to foster sustainable customer loyalty.